Pemberdayaan Ekonomi Kaum Perempuan GMIT Seydon Alor dengan Pendekatan Pendidikan Kristen Transformatif - Lao, Hendrik A.E; Ali, Umar; Koroh, Lanny Isabela Dwisyahri; Nani, Viktor (Devotion: Jurnal Pengabdian Masyarakat, 2024)
Community Service Activities carried out at GMIT Seydon Alor aim to empower women economically through Transformative Christian Religious Education by training in making bokasi fertilizer. The targets of the Community Service Activities are the women of GMIT Seydon Alor, totaling 75 women. The target of the activity is making bokasi fertilizer to improve the economy of women. Because their livelihood is agriculture. Outcomes from Community Service Activities at GMIT Seydon- Alor Regency. It can be concluded that the results of the activity had a good impact, as the women of GMIT Seydon were enthusiastic about making bokasi fertilizer and everyone was able to independently make bokasi fertilizer because so far they had difficulty getting fertilizer. The congregation, in this case the women, buy urea fertilizer from the shop and if urea fertilizer is used for a long period of time and continuously it can damage the nutrients in the soil. So, with community service activities carried out by the IAKN Kupang Postgraduate through education on making bokasi fertilizer, they realize that the surrounding environment can produce natural fertilizer. From the activities carried out for three days, the women of GMIT Syeidon Alor were able to produce bokasi fertilizer which can be used for their agriculture.